High-efficiency and low-consumption accumulator grid continuous casting forming process
Patent Information
- Application Number
- CN202611320525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]传统重力浇铸、间歇式浇铸工艺存在明显缺陷:开放式熔炼浇铸导致铅液氧化严重、铅烟量大、原料损耗高;冷却方式多为自然冷却或全程恒温水冷,结晶速率不可控,易造成表层晶粒过细、芯部晶粒粗大、组织不均,内部存在疏松、微气孔、夹杂缺陷;同时间歇生产效率低、一致性差、能耗高
1.本发明全程密闭熔炼、供液、铸轧,搭配惰性气体保护,铅液氧化损耗率降至1%以下,较传统工艺降低60%以上;分段闭环水冷循环利用热能,整体生产能耗降低35%以上,生产成本大幅降低。
Smart Images

Figure CN122999891A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, and in particular to a high-efficiency, low-consumption continuous casting process for battery grids. Background Technology
[0002] Lead-acid batteries are widely used in automotive starting, energy storage power stations, communication power supplies, and electric vehicles due to their advantages of safety, reliability, low cost, and high recyclability. The grid, as the core framework of the battery, undertakes the crucial functions of conductivity, carrying active materials, and corrosion resistance. Its purity, grain structure, density, and internal stress state directly determine the battery's lifespan and stability.
[0003] Traditional gravity casting and intermittent casting processes have obvious drawbacks: open melting and casting leads to severe oxidation of lead liquid, large amount of lead fumes, and high raw material loss; the cooling methods are mostly natural cooling or constant temperature water cooling throughout the process, the crystallization rate is uncontrollable, which easily causes the surface grains to be too fine, the core grains to be coarse, the structure to be uneven, and the internal structure to have looseness, micropores, inclusions and defects; at the same time, intermittent production has low efficiency, poor consistency and high energy consumption.
[0004] Current continuous casting processes generally employ simple filtration systems with only a single-layer filter, which cannot remove micron-sized fine oxide inclusions. Furthermore, the cooling methods often rely on a single constant-temperature cooling system, failing to differentiate temperature control based on the three stages of liquid flow, liquid-solid crystallization, and complete solidification of the grid. This results in uneven grain size, high residual stress, and limited improvement in corrosion resistance. Therefore, there is an urgent need to optimize high-precision multi-stage composite filtration systems and segmented gradient crystallization cooling processes to further enhance the overall performance of the grid. Summary of the Invention
[0005] To address the above problems, this invention discloses a high-efficiency, low-consumption continuous casting process for battery grids, comprising the following steps: (1) Precision closed melting of lead alloy: put lead-calcium-tin-aluminum alloy raw materials into a closed melting furnace according to the proportion, heat to 420-450℃ and melt at a constant temperature. Inert gas is introduced throughout the melting process to isolate oxidation. Stir at a constant temperature to obtain a lead alloy liquid with uniform composition and low oxidation. (2) Multi-stage composite filtration and vacuum degassing: Molten lead liquid is filtered through a three-stage structure consisting of a multi-layer woven 316L stainless steel mesh, a honeycomb porous silicon carbide ceramic filter plate, and a microporous alumina ceramic filter element. Combined with vacuum negative pressure degassing, large particles of slag, fine oxide inclusions, suspended impurities and encapsulated gas are removed layer by layer, so that the purity of lead liquid is ≥99.95%; (3) Constant temperature and pressure continuous closed liquid supply: After purification, the lead alloy liquid enters the closed heat preservation storage tank, and the temperature is controlled at 410-430℃ and the liquid supply pressure is 0.08-0.12MPa. The liquid supply is uniform and without fluctuation through the quantitative pressure stabilizing and guiding mechanism. (4) Multi-stage gradient closed-loop water-cooled continuous casting and rolling: When lead liquid enters the continuous casting and rolling mold, a three-stage differentiated closed-loop water-cooling temperature control mode is adopted, which includes rapid nucleation cooling at the inlet, steady-state crystallization temperature control in the middle section, and low-temperature solidification and crystal stabilization at the outlet. The water temperature is 35-40℃ at the inlet, 25-30℃ in the middle section, and 20-25℃ at the outlet. The exclusive cooling rate is matched at different solidification stages, and high-quality strip grid billet is obtained by continuous casting and rolling. (5) Online precision shaping and straightening: The plate blank is corrected for thickness and flatness by 5-7 sets of symmetrical flexible straightening rollers, and the thickness tolerance of the plate is controlled within ±0.02mm; (6) Low-temperature slow cooling stress setting: After shaping, the grid enters the constant temperature hot air slow cooling chamber and is cooled to room temperature at a uniform rate of 2-3℃ / min to completely eliminate the residual internal stress of casting and rolling, and obtain a finished grid with stable structure and no deformation defects.
[0006] In the above steps, the lead alloy liquid and the grid are produced and transferred in a relatively closed / independent chamber to avoid oxidation and leakage.
[0007] Preferably, in step (1), the mass ratio of each component of the lead-calcium-tin-aluminum alloy is: calcium 0.08%-0.12%, tin 0.3%-0.5%, aluminum 0.02%-0.05%, with the remainder being pure lead, and the purity of each component is ≥99.99%.
[0008] Preferably, in step (1), the inert gas is high-purity nitrogen, the gas flow rate is 8-12 L / min, the melting stirring speed is 30-50 r / min, and the constant temperature melting holding time is 20-30 min.
[0009] Preferably, the multi-stage composite filtration structure in step (2) is as follows: The coarse filter layer uses a multi-layer woven filter screen made of 316L stainless steel with a pore size of 0.8-1.2mm, which is used to intercept large particles of slag, oxide scale, and agglomerated impurities. The middle layer uses a honeycomb porous silicon carbide ceramic filter plate with a pore size of 0.15-0.25mm. It utilizes a through-cell honeycomb flow channel to achieve turbulent flow rectification and fine interception, removing micron-sized oxide inclusions. The deep filtration structure uses a microporous alumina ceramic filter element with a micropore diameter of 50-80μm to perform final homogenization and purification of the lead liquid and refine microscopic impurities. Vacuum degassing: vacuum degree -0.08 to -0.1 MPa, degassing time 10-15 min, effectively removing hydrogen and oxygen-encapsulated gases and microbubbles.
[0010] Furthermore, the principle and function of the three-stage gradient cooling technology in step (4) are as follows: Rapid cooling due to high temperature difference at the inlet: The water temperature is 35-40℃. The lead liquid is in a liquid flow state when it enters the mold. The moderate strong cooling quickly triggers a large number of uniform crystal nuclei, avoids the growth of large grain dendrites, and achieves rapid solidification and molding of the surface layer, preventing flow marks and edge collapse defects. Mid-stage steady-state crystallization uniform cooling: water temperature 25-30℃, the grid is in the liquid-solid coexistence crystallization stage, reducing the cooling temperature difference and slowing down the cooling rate, ensuring uniform growth of internal grains, eliminating core porosity and micropores, and achieving synchronous internal and external crystallization; Low-temperature stabilization and crystal cooling at the outlet section: water temperature 20-25℃, the grid is basically completely solidified, and the low-temperature stabilization cooling locks in the grain structure, refines the grain boundaries, reduces the overall residual stress, and avoids subsequent warping, deformation and springback defects.
[0011] Preferably, in step (5), the multi-stage precision straightening roller group includes 5-7 sets of symmetrically arranged stainless steel straightening rollers. The straightening process adopts flexible pressure adjustment, and the pressure of a single roller is controlled at 50-80N to avoid the grid being squeezed and deformed.
[0012] Preferably, in step (6), the slow cooling chamber adopts a hot air circulation constant temperature control structure with a constant internal wind speed of 0.5-1m / s to ensure uniform cooling of the entire grid area.
[0013] The battery grid prepared by the above process has uniform grain size, no internal pores or inclusions, and the corrosion resistance rate of the grid is reduced by more than 30% compared with the traditional cast grid. It is suitable for all types of valve-regulated and energy storage batteries.
[0014] The beneficial effects of this invention are as follows: 1. This invention features a fully enclosed smelting, liquid supply, and casting process, coupled with inert gas protection, reducing the lead molten metal oxidation loss rate to below 1%, which is more than 60% lower than traditional processes; segmented closed-loop water cooling utilizes thermal energy, reducing overall production energy consumption by more than 35% and significantly lowering production costs.
[0015] 2. This invention, through precise temperature control, stable pressure casting and rolling, and low-temperature slow cooling and shaping, produces grid grains that are uniform and dense, free from defects such as pores, inclusions, and cracks. It also features high dimensional tolerances, significantly improved corrosion resistance and mechanical strength, effectively avoiding grid corrosion and active material shedding during battery use, and increasing the battery cycle life by more than 25%.
[0016] 3. This invention operates in a completely closed system, with no lead fumes or dust leaking out, significantly reducing pollutant emissions. It eliminates the need for complex exhaust gas purification equipment, resulting in low environmental treatment costs and a safe and clean production environment. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the production process of the present invention; Figure 2 This is an experimental comparison table for the present invention. Detailed Implementation
[0018] The present invention will be further illustrated below with reference to the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0019] like Figure 1 The steps shown are used to produce the grid plates for Examples 1 and 2. Example 1
[0020] A high-efficiency and low-consumption continuous casting process for battery grids includes the following steps: 1. Precision melting of lead alloy: According to the ratio of calcium 0.1%, tin 0.4%, aluminum 0.03%, and the balance pure lead, the alloy is put into a closed melting furnace, heated to 435℃ and melted at a constant temperature. High-purity nitrogen gas is introduced for protection at a flow rate of 10L / min and a stirring speed of 40r / min. The mixture is held at this temperature for 25min to obtain a uniform and stable lead alloy liquid.
[0021] 2. Multi-stage degassing and filtration: The lead alloy liquid is first filtered through a 1.0mm coarse filter, then through a 0.2mm fine ceramic filter for deep filtration, and then introduced into a vacuum degassing device with a vacuum degree of -0.09MPa for 12 minutes, achieving a lead liquid purity of 99.96%.
[0022] 3. Constant temperature and pressure continuous liquid supply: After purification, the lead liquid is introduced into the heat-insulated storage tank, and the temperature is controlled at 420℃ and the liquid supply pressure is 0.1MPa. The liquid is supplied continuously at a uniform speed through a quantitative guide mechanism.
[0023] 4. Closed-loop water-cooled continuous casting and rolling: control the die running speed to 8m / min, the cooling water flow rate to 18m³ / h, and control the temperature in sections: 38℃ for the inlet section, 28℃ for the middle section, and 22℃ for the outlet section. Continuous casting and rolling yields strip-shaped grid billets.
[0024] 5. Online precision straightening: Six sets of stainless steel straightening rollers are used, with a single roller pressure of 65N, to straighten the grating blank as a whole, and the thickness tolerance is controlled within ±0.02mm.
[0025] 6. Low-temperature slow cooling and shaping: The shaped grid is sent into a slow cooling chamber, and the cooling rate is controlled at 2.5℃ / min with an air velocity of 0.8m / s inside the chamber. The grid is cooled to room temperature evenly to eliminate internal stress and obtain the finished grid. Example 2
[0026] A high-efficiency and low-consumption continuous casting process for battery grids includes the following steps: 1. Precision melting of lead alloy: Feed the materials according to the ratio of calcium 0.08%, tin 0.35%, aluminum 0.02%, and the balance pure lead, heat to 425℃ and melt at a constant temperature, with nitrogen flow rate of 8L / min, stirring speed of 35r / min, and holding for 20min.
[0027] 2. Multi-stage degassing and filtration: The lead liquid is filtered sequentially through a 0.8mm coarse filter and a 0.15mm ceramic filter, and degassed under a vacuum of -0.08MPa for 10 minutes, resulting in a purity of 99.95%.
[0028] 3. Constant temperature and pressure continuous liquid supply: The liquid storage tank temperature is 410℃, the liquid supply pressure is 0.08MPa, and the liquid is supplied continuously in a metered manner.
[0029] 4. Closed-loop water-cooled continuous casting and rolling: mold linear speed 6m / min, cooling water flow rate 15m³ / h, inlet water temperature 35℃, middle section 25℃, outlet 20℃, continuous casting and rolling forming.
[0030] 5. Online precision straightening: 5 sets of straightening rollers, single roller pressure 50N, to accurately calibrate the flatness and thickness of the grid.
[0031] 6. Low-temperature slow cooling and shaping: The cooling rate is 2℃ / min, the air velocity in the chamber is 0.5m / s, and the material is uniformly and slowly cooled to room temperature to complete the preparation.
[0032] Comparative Example 1 The same specifications of battery grids are produced using the traditional gravity intermittent casting process, which includes conventional smelting, open casting, natural cooling, and manual shaping.
[0033] Performance test results The grids prepared in Examples 1 and 2, and the corresponding assembled batteries in the comparative examples, were subjected to performance testing. The results are as follows: 1. Production efficiency: The production capacity of Examples 1 and 2 increased by 82% and 78% respectively compared to the control group; 2. Lead loss: The lead loss rates in Examples 1 and 2 were 0.8% and 0.9%, respectively, while the loss rate in the comparative example was 3.2%. 3. Grid performance: The grid prepared by the process of this invention is free of pores and cracks, improves grain uniformity by 45%, reduces corrosion rate by 32% and 29%, and increases tensile strength by 28% and 25%; 4. Battery life: The cycle life of the batteries in Examples 1 and 2 is increased by 26% and 23% respectively compared to the comparative example, which can be combined with... Figure 2 refer to; 5. Energy consumption indicators: The energy consumption of the process of this invention is reduced by 38% and 35% compared with the traditional process.
[0034] Comparative Example 2 (same operating conditions, same equipment, but using constant temperature cooling throughout the process) To verify the inventiveness and superiority of the segmented gradient cooling method of this invention, a control experiment was conducted under the premise that all raw materials, melting parameters, filtration parameters, liquid supply parameters, straightening parameters, and production speeds were completely consistent. The entire process was kept at a constant water temperature of 28°C without segmented temperature difference control, and all other processes were completely identical.
[0035] The performance comparison test results, under completely identical production conditions, show the following performance comparison between segmented gradient cooling and constant temperature cooling: Internal defects: The segmented cooling of this invention results in no pores, no looseness, no intergranular voids, and a dense structure; the isothermal cooling control group shows a small amount of micro-looseness, localized coarse grains, and trace amounts of solidification shrinkage cavities in the core of the grid.
[0036] Grain uniformity: Segmented cooling: Grain size difference <8%, overall refinement and uniformity; Isothermal cooling: Grain size difference >35%, obvious microstructure gradient.
[0037] Corrosion resistance: Segmented cooling: Corrosion rate is reduced by 31% compared to traditional processes; Constant temperature control group: Corrosion rate is reduced by only 12%.
[0038] Mechanical stability and deformation rate: Segmented cooling: No residual stress, no warping when placed; Constant temperature control group: Slight residual stress exists, and the probability of micro-deformation of finished products is increased by 18%.
[0039] Battery cycle life: Segmented cooling process: Cycle life increased by 25%; Constant temperature cooling control group: Cycle life increased by only 9%.
[0040] Experimental results demonstrate that single constant-temperature water cooling cannot meet the crystallization requirements of different solidification stages of lead liquid, easily causing an imbalance in the crystallization rate between the surface and the core, resulting in structural defects and residual stress. In contrast, the three-stage gradient cooling of this invention achieves controllable nucleation, balanced crystallization, refined grains, and stress elimination through precise temperature control in stages, demonstrating significant technical advantages and inventiveness.
[0041] Test results show that the process of this invention has significant advantages over traditional processes in terms of production efficiency, cost control, product performance, environmental protection and energy saving, and the product quality stability is greatly improved, making it suitable for large-scale industrialization.
[0042] The technical means disclosed in this invention are not limited to those disclosed in the above embodiments, but also include technical solutions composed of any combination of the above technical features.
Claims
1. A high-efficiency, low-consumption continuous casting process for battery grids, characterized in that, Includes the following steps: Step 1: The lead-calcium-tin-aluminum alloy raw material is uniformly melted at a constant temperature of 420-450℃ under a protective atmosphere to obtain a preliminary lead alloy liquid; Step 2: Under negative pressure, the initial lead alloy liquid passes through a deep filtration structure consisting of a 316L stainless steel multi-layer woven filter screen, a honeycomb porous silicon carbide ceramic filter plate, and a microporous alumina ceramic filter element to obtain a ready-to-use lead alloy liquid. Step 3: The spare lead alloy liquid is stored in a storage tank at 410-430℃ and continuously transported outward at 0.08-0.12MPa; Step 4: The lead alloy liquid is fed into the continuous casting and rolling mold. A three-stage differentiated closed-loop water cooling temperature control mode is adopted, which includes rapid nucleation and cooling at the inlet, steady-state crystallization temperature control in the middle section, and low-temperature stabilization and crystallization at the outlet. The water temperature is 35-40℃ at the inlet, 25-30℃ in the middle section, and 20-25℃ at the outlet to obtain the grid billet. Step 5: The grid blank is rolled by multiple sets of flexible straightening rollers to correct its thickness and flatness. The thickness tolerance of the grid is controlled within ±0.02mm. Step 6: The grid blank is then placed into a constant temperature hot air slow cooling chamber and cooled to room temperature at a uniform rate of 2-3℃ / min to obtain the grid product; In the above steps, both the lead alloy liquid and the grid are carried out in separate chambers.
2. The high-efficiency and low-consumption continuous casting process for battery grids according to claim 1, characterized in that, In step one, the mass ratio of each component in the lead-calcium-tin-aluminum alloy is as follows: calcium 0.08%-0.12%, tin 0.3%-0.5%, aluminum 0.02%-0.05%, with the balance being pure lead. The purity of each component is ≥99.99%.
3. The high-efficiency and low-consumption continuous casting process for battery grids according to claim 1, characterized in that, In step one, the protective atmosphere is nitrogen, the gas flow rate is 8-12 L / min, the stirring speed is 30-50 r / min, and the constant temperature melting and holding time is 20-30 min.
4. The high-efficiency and low-consumption continuous casting process for battery grids according to claim 1, characterized in that, In step two, the pore size of the 316L stainless steel multilayer woven filter screen is 0.8-1.2mm, the pore size of the honeycomb porous silicon carbide ceramic filter plate is 0.15-0.25mm, and the micropore size of the microporous alumina ceramic filter element deep filtration structure is 50-80μm. The vacuum degassing degree is -0.08 to -0.1MPa, and the degassing time is 10-15min.
5. The high-efficiency and low-consumption continuous casting process for battery grids according to claim 1, characterized in that, Step five involves 5-7 sets of symmetrically arranged stainless steel straightening rollers. The straightening process uses flexible pressure adjustment, with the pressure of a single roller controlled at 50-80N.
6. The high-efficiency and low-consumption continuous casting process for battery grids according to claim 1, characterized in that, In step six, the slow cooling chamber adopts a hot air circulation constant temperature control structure, with the internal wind speed remaining constant at 0.5-1m / s.
7. A battery grid prepared according to any one of claims 1-6, characterized in that, The grid has uniform grain size and no internal defects such as pores or inclusions. The corrosion rate of the grid is reduced by more than 30% compared with traditional cast grids, making it suitable for all types of valve-regulated and energy storage batteries.
